The Role of Posyandu Activities Program in Improving Mother and Child Health in Mulung Village, Driyorejo District, Gresik Regency - Faristasari, Anasya Salsa; Dealova, Rihlah Zulfa Izza; Tamam, Ayat Akhras; Mawaddah, Annisatul (Jurnal Paradigma, 2025)
Integrated Service Post (Posyandu) is a community-based innovation developed to support national health programs. Posyandu is designed as a place for basic health services that involves active community participation, especially health cadres, in providing health, nutrition and immunization services. This research aims to explore the role of the posyandu program in improving maternal and child health, identify the challenges faced, and offer solutions for optimizing the function of posyandu as a pillar of community-based health. This research is expected to contribute to the development of more effective policies and practices in the future. This research approach uses qualitative methods, and data collection is carried out through in-depth interviews and participant observation. This research was conducted at one of the posyandu in Mulung village, Driyorejo District, Gresik Regency, East Java. The research results show that incentives and ongoing training are needed to increase cadres' motivation in carrying out their duties. With a more comprehensive approach and strong support from all parties, it is hoped that maternal and infant mortality rates can be reduced and the problem of malnutrition can be overcome effectively.